Power flow control of a multi-bus/three-feeder distribution system using generalized unified power quality conditioner - Mohammed, B.S. (Korean Institute of Electrical Engineers, 2015)
This paper analyses the power flow of a three-feeder/multi-bus distribution system by a custom Generalized Power Quality Conditioner (GUPQC). The GUPQC has been realized by three voltage source converters (VSCs) coupled back-to-back through a common DC-link capacitor on the DC-side. One feeder was controlled by the shunt compensator, whereas each of the other two feeders was controlled by the proposed novel series compensator. The GUPQC has the capability to simultaneously compensate voltage and current quality problems of a multi-bus/three-feeder distribution system. Besides that, the power can be transferred from one feeder to other feeders to compensate for poor power quality problems. Extensive simulation studies were carried out by using MATLAB/SIMULINK software to establish the ability of the GUPQC to improve power quality of the distribution systems under distorted supply voltage conditions. Â© The Korean Institute of Electrical Engineers.